An Inclusion Complex of C60 with Organosilylated γ‐Cyclodextrin: Drastic Enhancement of Apparent Solubility of C60 in Nonpolar and Weakly Polar Organic Solvents. Issue 1 (13th December 2012) - Takeda, Youhei; Nagamachi, Toshiki; Nishikori, Katsuaki; Minakata, Satoshi
<x xml:space="preserve">Abstract</x> What a solution! A bi‐capped inclusion complex of C60 with organosilylated γ‐cyclodextrin that is highly soluble in nonpolar and weakly polar organic solvents, such as CHCl3 or cyclohexane, was prepared and characterized. The complex facilitates the separation of C60 from C70 and selective functionalization of C60. Furthermore, fabrication of a thin film of the complex by using a solution technique was demonstrated.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>